Denatured Collagen Modulates the Phenotype of Normal and Wounded Human Skin Equivalents - Egles, Christophe (2008)
Epithelial–mesenchymal interactions are known to play an important role in modulating homeostasis and repair. However, it remains unclear how the composition of the extracellular matrix may regulate the ability of dermal fibroblasts to engage in such cross talk. To address this, we studied how fibroblast phenotype was linked to the behavior of normal and wounded human skin equivalents (HSE) by comparing human dermal fibroblasts (HDF) incorporated into the three-dimensional tissues to those extensively cultivated in two-dimensional (2D) monolayer culture on denatured collagen (DC) matrix, native collagen, or tissue culture plastic before incorporation into HSEs. We first established that prolonged passage and growth of HDF on DC increased their migratory potential in a 2D monolayer culture. When HDF variants were grown in HSEs, we found that extended passage on DC and incorporation of DC directly into the collagen gel enhanced proliferation of both HDF and basal keratinocytes in HSEs. By adapting HSEs to study wound reepithelialization, we found that the extended passage of HDF on DC accelerated the rate of wound healing by 38%. Thus, extensive ex vivo expansion on DC was able to modify the phenotype of skin fibroblasts by augmenting their reparative properties in skin-like HSEs.